2003
DOI: 10.1149/1.1570822
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Electrochemical Characteristics of Aluminum Anodized Film Formed in Ammonium Adipate Solution

Abstract: The morphology, chemical composition, and crystal structure of aluminum anodized films formed in 85°C aqueous ammonium adipate electrolyte at various forming voltages ͑20-200 V͒ were investigated. The relationship between the microstructure and the electrochemical behavior of the anodized oxide film was also explored. The results showed that an amorphous oxide film was formed when the forming voltage was 100 V or lower. Both the increase of film thickness per increase in voltage and the relative dielectric con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…It has been found that a uniform distribution of Al and O existed within the oxide formed by single-stage anodization of aluminum in ammonium adipate electrolyte. 25 Thus, the concentration gradient revealed in Fig. 4(b) seemed to result from the re-anodization stage.…”
Section: A Current and Voltage Transients During Anodizationmentioning
confidence: 87%
See 3 more Smart Citations
“…It has been found that a uniform distribution of Al and O existed within the oxide formed by single-stage anodization of aluminum in ammonium adipate electrolyte. 25 Thus, the concentration gradient revealed in Fig. 4(b) seemed to result from the re-anodization stage.…”
Section: A Current and Voltage Transients During Anodizationmentioning
confidence: 87%
“…The results confirmed that it was ␥Ј-Al 2 O 3 with FCC structure. 25,26,31 The results demonstrated that the heat treatment could induce amorphous-to-crystalline transformation for the aluminum anodic oxide film. Interestingly, the induced crystalline formation predominantly occurred in the outer layer of the oxide.…”
Section: A Current and Voltage Transients During Anodizationmentioning
confidence: 94%
See 2 more Smart Citations
“…Anodic films, composed, in specially, of amorphous alumina, are formed by application of an anodic potential *email: Lidia Benea@ugal.ro to aluminum sheet which is immersed in a suitable electrolytes. When are used slightly alkaline electrolytes or close to neutrality due to lowest solubility of the oxide, a compact oxides (barrier-type layer) are usually generated [12]. In contrast, when the solubility of the oxide is increased, porous oxide layers can be formed [10].…”
mentioning
confidence: 99%